The Method in Understanding Hadith Through Ijmā' and Its Implications for Islamic Law in Indonesia: Studies on the Hadiths of the Month of Qamariyah - Majid, Abdul; Sagirah, Sitti; Wendry, Novizal; Safri, Edi; Syafruddin, Syafruddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This study examines the approach used in comprehending hadith through ijmā’  and its ramifications for Islamic law in Indonesia, especially the hadiths of the month of Qamariyah. This is an ahkam hadith study that employs hadith science and Islamic law theory, particularly ijmā'. This study reaches the following conclusions: Firstly, there are varieties of approaches for comprehending the customs of the month of Qamariyah, particularly in defining the month of fasting and holidays in Indonesia, which is seen as essential. This interpretation triggers the emergence of a two-poled, textual and contextually distinct views of Islamic law. Although such discrepancies can tarnish Islamic symbols, it is believed that they would spark social discord in Indonesian culture. Second, ijmā’  as a source and method of interpreting Islamic law can be used to prevent the susceptibility of social conflicts in society, particularly when debates go beyond ethical principles. Otherwise, this concern worsens when it is used by agents both individuals and groups, who frequently exploit the current circumstances for their own political gain and ultimately polarize and divide society socially. Thirdly, the ijmā' conducted by the government during the isbath session with the participation of all religious organizations in Indonesia, including MUI, NU, Muhammadiyah, DDII, PERSIS, and Al-Washliyah, is a positive development for the certainty and benefit of Islamic law. Hence, the ijmā' approach of analyzing hadith is consistent with Islamic legal standards. Musāyarah bi al-maṣāliḥ al-nās signifies that the determination of a law must be in accordance with human benefits, both individually and socially, particularly within the context of the state.